(untitled) (Revista de Ensino em Artes, Moda e Design, 2020)
This article reports the methodological experience in two design disciplines in the Bachelor in Fashion Design course. In both cases, the project is carried out from the meeting with people who are not from the area. Following the conception that design is an interdisciplinary field, multiple voices are fundamental for the formation of a designer who works on building a more fair and respectful society. In order to theoretically base the methodologies proposed in the disciplines, it starts from participatory design up to contemporary lines, which seek to expand both ways of making design and its fields of activity.